LITERATUR REVIEW: TERAPI NON FARMAKOLOGIS UNTUK MENINGKATKAN KUALITAS TIDUR PASIEN DI ICU ATAU CCU: Literatur Review: Non-Pharmacological Therapy for Increasing Sleep Quality of Patients in ICU or CCU - Rizky Asta Pramestirini; Heny Ekawati; Suhariyati Suhariyati (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2021)
Abstract Sleep is one of the basic human needs. Good quality sleep can increase the improvement of the disease. Sleep disturbances are common among hospitalized patients in CCU and ICU. The purpose of this literature review is to compare several research results on non-pharmacological therapies (eye masks, earplugs, music therapy, turning off lights, environmental modifications) in improving sleep quality to determine the best nursing action and safe for treating sleep disorders patients. Search articles using the PICO framework in the database; Google Scholar, Ebscho, Science direct, Elseiver, MedLine, CINAHL, PubMed, and ProQuest, limited to the last 10 years; 2011 to 2021, 10 International Journals were obtained. Improved sleep quality can be done in several ways; the use of eye masks, earplugs, music therapy, light and sound reduction, switching treatment schedules outside of bedtime, and combinations. The results of the review show schedules outside of bedtime, and combinations. The results of the review show that the most effective actions applied locally to improve sleep quality are reducing lighting and noise and diverting treatment schedules outside of bedtime because it is easy, safe, and does not cost money. If the intervention has not helped, eye masks, earplugs, and/or music can be offered according to the patient's choice, local culture, and facilities available at the hospital. Further research is needed on patients outside the ICU/CCU with a larger number of samples, different age and condition characteristics, longer treatment duration, and using objective sleep quality measurement tools such as polysomnography.